Pheophorbide a: State of the Art - Assunta Saide; Chiara Lauritano; Adrianna Ianora (Marine Drugs, 2020)
Chlorophyll breakdown products are usually studied for their antioxidant and anti-inflammatory activities. The chlorophyll derivative Pheophorbide a (PPBa) is a photosensitizer that can induce significant anti-proliferative effects in several human cancer cell lines. Cancer is a leading cause of death worldwide, accounting for about 9.6 million deaths, in 2018 alone. Hence, it is crucial to monitor emergent compounds that show significant anticancer activity and advance them into clinical trials. In this review, we analyze the anticancer activity of PPBa with or without photodynamic therapy and also conjugated with or without other chemotherapic drugs, highlighting the capacity of PPBa to overcome multidrug resistance. We also report other activities of PPBa and different pathways that it can activate, showing its possible applications for the treatment of human pathologies.